Association between menopause and lumbar disc degeneration: an MRI study of 1, 566 women and 1, 382 men. Issue 10 (October 2017) - Lou, Chao; Chen, Hongliang; Mei, Liangwei; Yu, Weiyang; Zhu, Kejun; Liu, Feijun; Chen, Zhenzhong; Xiang, Guangheng; Chen, Minjiang; Weng, Qiaoyou; He, Dengwei
Abstract: Objective: The aim of this study was to revisit and further investigate the association between menopause and disc degeneration in the lumbar spine using a magnetic resonance imaging-based eight-level grading system. Methods: This study cohort comprised of 1, 566 women and 1, 382 age-matched men who were admitted for low back pain from June 2013 to October 2016. Data on age, weight, height, body mass index, age at natural menopause, and years since menopause (YSM) were obtained. Lumbar disc degeneration was assessed using a magnetic resonance imaging-based eight-level grading system. Results: After adjustment for the confounding factors of age, height, and weight, young age-matched men were more susceptible to disc degeneration than premenopausal women ( P  < 0.05). However, after menopause, postmenopausal women had a significant tendency to develop more severe disc degeneration than their age-matched men ( P  < 0.05), and also compared with premenopausal and perimenopausal women ( P  < 0.01). Postmenopausal women were divided into nine subgroups by every 5 YSM. When YSM was less than 15 years, a positive trend was observed between YSM and severity of disc degeneration, respectively, at L1/L2 ( r  = 0.241), L2/L3 ( r  = 0.193), L3/L4 ( r  = 0.191), L4/L5 ( r  = 0.165), L5/S1 ( r  = 0.153), and all lumbar discs ( r  = 0.237) ( P  < 0.05 or 0.01). The analysis of covariance indicated a significant difference in each disc level ( P  < 0.05 or 0.01) between every two groups. When YSM was more than 15 years, the significant difference, however, disappeared in each disc level ( P  > 0.05). Conclusions: Menopause is associated with lumbar disc degeneration. The association occurred in the first 15 YSM, suggesting estrogen deficiency might be a risk factor of disc degeneration of the lumbar spine. Further studies need to be carried out for deciding whether age or menopause plays a more important role in the progression of disc degeneration in the lumbar spine.